Accounting and Reporting in Supporting the Transition to a Circular Economy: a Bibliometric Analysis - Yuliia Maksymiv; Nadiia Skromyda; Jurij Urbancic (Journal of Vasyl Stefanyk Precarpathian National University)
The development of a circular economy is an important task for socially responsible politicians, scientists and businesses. Despite growing interest in this concept over the past decade, the implementation of circular business models remains limited. One of the key barriers is the insufficient utilization of accounting and reporting capabilities, which are practical tools for transitioning to a circular economy. These tools support informed managerial decision-making in building and maintaining circular business models and processes. To explore the scientific interest in accounting and reporting as a means of supporting the transition to and development of a circular economy, a bibliometric analysis was conducted. This analysis utilized data from the Scopus database (845 documents from 2004 to 2024) and was further processed using VOSviewer to construct maps based on bibliographic data. The data allowed for the identification of authors and their collaboration clusters, dominant publications and regions in the research field, as well as important directions for further studies. The clustering of the conceptual landscape under study revealed seven keyword-based clusters and their interconnections, highlighting research priorities. It was established that, despite significant progress in the theoretical development of the circular economy from an interdisciplinary perspective, organizational and economic tools—particularly accounting and reporting—remain underexplored. The findings indicate the significant potential of accounting and reporting, which must be considered in the training of socially responsible accountants, financiers, and managers. The study emphasizes the need for further adaptation of accounting and reporting to meet the requirements of the circular economy, thereby contributing to achieving the Sustainable Development Goals.